Tingkat Pengetahuan Masyarakat tentang Perilaku Hidup Bersih dan Sehat di Desa Rumengkor Kabupaten Minahasa - Vina Putri Patandung; Mareyke Yolanda Lusia Sepang; Meylani Dewi Wowor (PT.Mantaya Idea Batara, 2022)
Background: Clean and Healthy Lifestyle (PHBS) is very important for health, life, and development. Worldwide an estimated 2.4 billion people still lack basic sanitation. PHBS is a concern for the government because it becomes a benchmark for increasing health coverage in the SDGs program in 2015-2030. PHBS and SDGs are one of the prevention efforts that can have a short-term impact on improving health, including the family, the general public, and schools. The knowledge and awareness of the community, especially the people who live in the village are still relatively low to get used to having a clean and healthy life. The purpose of this study was to determine the level of public knowledge about PHBS in Rumengkor Village, Minahasa Regency. Method: Descriptive quantitative to describe the level of community knowledge about PHBS. The sample was the people of Rumengkor Village, Minahasa Regency, who are respondents from 78 people, which are determined using purposive sampling. Data were obtained by interview and using demographic characteristics questionnaire and PHBS questionnaire. Results: In general, the level of public knowledge about PHBS for clean water facilities, the availability of healthy latrines, waste disposal, fruit and vegetable consumption is good, but the level of knowledge about smoking habits is still very low. Conclusion: The results of this study illustrate the level of community knowledge about PHBS in Rumengkor Village is quite good. It's just that PHBS related to smoking habits are still relatively lacking. This happens because most of the respondents and family members are active or passive smokers. Recommendations for health workers are expected to be more active in providing health education in easily accessible language so that people can understand and make good use of the information received.